Purification and Evaluation of Bioactive Fractions for Anti-Cancer Potentials from the Flowers and Leaves of Nyctanthes arbor-tristis L. - Bibechana Timsina (Science Faculty of Chiang Mai University, 2019)
This study aims at the extraction of bioactive metabolites from the flowers and leaves of parijat (Nyctanthes arbortristis Linn.) and evaluation of their cytotoxic properties on HeLa cells, HepG2 cells and also on normal human peripheral lymphocytes. The flowers and leaves of parijat were collected from Bangalore and the bioactive compounds were extracted from the dried plant parts using ethanol and also by aqueous extraction methods. The antiproliferative effects of the extracts were evaluated on the cancer cell lines HeLa and HepG2 and cytotoxicity were checked on normal human lymphocytes by MTT assay. The extracts were further purified by TLC and characterized by LC-MS method.The ethanol and aqueous extracts of both the plant parts had significant cytotoxicity to HeLa and HepG2 cells. By thin layer chromatography we could isolate six fractions each from the flower extract and the leaf extract, out of which fraction 3 from the flower and fraction 5 from the leaves have exhibited maximum antiproliferative effects with an IC50 value of 10 mg/ml on HeLa cells, 5 mg/ml on HepG2 cells and > 200 mg/ml on normal lymphocytes, indicating that they are least toxic to the healthy cells. By LC-MS analysis, the bioactive fractions were found to have m/z values of 809 (3rd fraction from flower) and 922 (5th fraction from leaves) indicating that these are novel ones. Here parijat flowers and leaves have shown promising results as potential sources for the isolation of a bioactive compounds with anticancer activities.